Software Design Methodology - Zhu, Hong (Elsevier, 2005)
Software design methodology has come a long way since the 1960s and 1970s when programmers were limited to Pascal/C and SA/SD to create systems. When creating information systems for today's world, many factors must be taken into consideration including globalization, the software lifecycle, modeling, coding, testing, and maintenance.